2021
DOI: 10.3390/nu14010013
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Trajectories of Macronutrient Intake and Their Associations with Obesity among Chinese Adults from 1991 to 2018: A Prospective Study

Abstract: Studies on macronutrient intake and obesity have been inconclusive. This study examined the associations between multi-trajectories of macronutrients and the risk of obesity in China. We used data from 7914 adults who participated in the China Health and Nutrition Survey at least three times from 1991 to 2018. We collected detailed dietary data by conducting three 24 h dietary recalls and weighing foods and condiments in household inventories. We identified multi-trajectories using group-based multi-trajectory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 44 publications
2
3
0
Order By: Relevance
“…Similarly, over the decades, the diet of Chinese adults has undergone significant changes, characterized by a decrease in the intake of grains and vegetables and an increase in the intake of animal foods 18 . Consistent with previous studies, we found that the Chinese population as a whole showed a decrease in the proportion of carbohydrate energy intake, an increase in the proportion of fat energy intake, and a stable proportion of protein energy intake in a small range 19 . In addition, there was a larger part of the population in the normal macronutrient range.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Similarly, over the decades, the diet of Chinese adults has undergone significant changes, characterized by a decrease in the intake of grains and vegetables and an increase in the intake of animal foods 18 . Consistent with previous studies, we found that the Chinese population as a whole showed a decrease in the proportion of carbohydrate energy intake, an increase in the proportion of fat energy intake, and a stable proportion of protein energy intake in a small range 19 . In addition, there was a larger part of the population in the normal macronutrient range.…”
Section: Discussionsupporting
confidence: 90%
“… 28 A study of the Chinese population showed that macronutrient intake was associated with obesity, and consistent with this study, the study also selected a balanced macronutrient group as the control group and thought that relatively low carbohydrate and high fat intake may be beneficial in preventing obesity. 19 Obesity is thought to be the promoter of T2DM, 29 which indirectly supports the conclusions of this study.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“… Phillips et al (2013) reported that total energy intake, the macronutrient composition of the diet, and physical activity level were insignificantly different between the metabolically healthy and unhealthy groups regardless of the BMI. Another opinion from China reported that relatively high-carbohydrate and low-fat intakes were associated with a higher risk of obesity development in rural Chinese adults ( Zhang et al, 2022 ). In daily clinical practice, it may be worthy to do the dietary assessment during obesity evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…To date, studies which examined dietary trajectories have used different diet parameters to model dietary trajectories. In recent years, the use of empirically derived (generated) dietary patterns and dietary indices appears to be the most common (10)(11)(12)(13) , although some studies have chosen to focus on specific food groups (9,14) or nutrients (15) .…”
mentioning
confidence: 99%